The impact of library automation on the library staff and library services of EDSOR consortium schools - Gabiola, April M.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
Computers have been present in the libraries since its introduction to offices in the early 1990s. Most of today's academic libraries already shifted to automation. School libraries, on the other hand are not being left behind. Numerous studies were done with regards to the impact of automation on the users of a library and only a few focused on the library personnel. It is in this light that his study centered on how library automation affects the library staff of three of the EDSA-Ortigas Consortium Schools - Immaculate Conception Academy, La Salle Greenhills, and Xavier School.
Of the 43-library staff of the three schools, 23 responded to the survey questionnaire. The data gathered from the survey and follow-up questions revealed that the library staff of the three schools have positive feelings towards the implementation of automation. Sixteen, or 69.56% of the respondents said that there was an increased feeling of usefulness, 19 of 82.61% were satisfied with their jobs, and 12 or 52.17% of the respondents claimed that there was an increased sense of achievement after automation. Of the total number of respondents, 17 (73.91) viewed automation as an opportunity to learn and develop their skills. More than half (77.27%) of the respondents claimed increase efficiency, simplified jobs, and that their tasks were done in a shorter span of time. Typewriters were replaced by computers which made them perform their tasks more conveniently. All three schools used Windows-based OPACs, offered internet service, used student ID as library cards, and used barcodes. These changes both reduced and increased the number of tasks of the library staff. Although some tasks have been automated, tasks such as cataloging, and inventory remained partly manual.
Along with the innovations in the library are problems. Respondents' top problem was the slow/old/outdated computers (56.25%). Other problems include the inappropriate/insufficient software and some problems regarding borrow and return transaction. Fifty-six percent (55) of the respondents perceived that their workplace is fully-automated, all of which said that full automation improved their organization. Forty four percent (45) thinks that their library is not yet fully-automated, all of which recommended full automation.
The researcher recommended that a similar study be done among other schools especially that of the public-school libraries and public schools. Also, the researcher suggested an internal study among the EDSOR Consortium Schools to better assess the impact of automation on the library staff and to better address the problems encountered.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: EDSA Ortigas Consortium Schools; Immaculate Conception Academy; La Salle Greenhills; Xavier School; School libraries -- Automation